Una propuesta didáctica para la enseñanza de los conceptos estructurantes de discontinuidad de la materia y unión química desde la epistemología y la historia de la ciencia contemporáneas - Mosquera S., Carlos J.; Ariza A., Leidy G.; Reyes G., Andrea M.; Hernández R., Carlos (Revista Científica, 2011)
This didactic proposal is oriented towards the educational problems about the relationship between atomic structure and macroscopic properties that shows matter in the solid, liquid and gas states, using structural concepts of corpuscular nature of the matter and chemical bond. It’s construction is product of a theoretical analysis of antecedents referred to diverse aspects such as: history of chemistry, science epis- temology, constructivism, problem solving didactic model, cognitive psychology and relationships STS, it is presented in a didactic unit made up of seven activities, including the previous knowledge analysis of the students, five teaching-learning activities and a final activity in which the reach of skills is evaluated along the application of the proposal.